Aplicação do índice de pobreza multidimensional na avaliação da efetividade de programas habitacionais de interesse social na Amazônia: Residencial Cachoeirinha-Manaus-AM - Cordeiro, Janaina da SIlva (Brasil, 2024)
The lack of basic sanitation, especially in the Amazonas region, represents a significant challenge that hampers quality of life and intensifies risks to public health and water resource contamination. Thus, this study aimed to analyze the impacts of post-occupation environmental sanitation interventions of the PROSAMIM Program on the quality of life of the Cachoeirinha Residential community in Manaus-AM. The Multidimensional Poverty Index (MPI) was used as an analytical tool, following the Alkire-Foster method developed by Sabina Alkire and James Foster (2007). It revealed that the interventions implemented by the PROSAMIM Program were essential in providing better housing conditions and improving urban infrastructure. However, the need to strengthen local sense of belonging remains an essential challenge to ensure a complete and sustainable transformation in residents' quality of life. The use of MPI proved crucial in identifying priority areas and strategically allocating resources, resulting in improvements in occupational stability. MPI stood out as a public management tool, as it allows for not only economic analysis but also considers various dimensions of poverty, providing a comprehensive view of community needs. It is strongly recommended that public officials use MPI to guide more effective and inclusive policies, aiming for a substantial transformation in the quality of life of families in vulnerable situations.